GATA2 participates in protection against hypoxia-induced pulmonary vascular remodeling. - Yuko Shirota; Shin'ya Ohmori; James Douglas Engel; Takashi Moriguchi (PLoS ONE)
The vascular endothelium is vital for cardio-pulmonary homeostasis and, thus, plays a crucial role in preventing life-threatening lung diseases. The transcription factor GATA2 is essential for hematopoiesis and maintaining vascular integrity. Heterozygous mutations in GATA2 can lead to a primary immunodeficiency syndrome with pulmonary manifestations. Some GATA2 haploinsufficient patients develop pulmonary hypertension (PH), characterized by vascular remodeling and occlusion of small pulmonary arteries. However, the mechanism underlying pulmonary vascular remodeling in GATA2 haploinsufficient patients remain unclear. To understand how GATA2 deficiency affects pulmonary artery homeostasis, we applied a chronic hypoxia-mediated PH model using inducible systemic Gata2 conditionally deficient (G2-CKO) mice. The G2-CKO mice exhibited augmented pulmonary vascular remodeling, with enhanced α-smooth muscle actin accumulation and increased apoptotic cells in the vascular wall upon chronic hypoxia. Transcript analysis and chromatin immunoprecipitation assays using mouse pulmonary vascular endothelial cells revealed that GATA2 directly regulates the expression of G6pdx (a crucial cytoprotective enzyme) and Bmp4 (a growth factor that mediates vascular homeostasis). These results suggest that GATA2-deficient lungs are vulnerable to the hypoxic stress due to a diminished cellular protective response, making G2-CKO mice more prone to vascular remodeling upon chronic hypoxia. These findings provide insights into the mechanisms underlying GATA2-haploinsufficiency-related pulmonary hypertension.